IMPLICATION OF CLASSROOM CLIMATE AND GENDER ROLE TO THE ACADEMIC PERFORMANCE OF LABORATORY HIGH SCHOOL - Favor, Dr (PEOPLE: International Journal of Social Sciences, 2017)
This study was conducted in response to the mandate of Globalization as the Philippines take part in the ASEAN INTEGRATION. A descriptive evaluative analysis was utilized that focuses on satisfaction levels of students on the effect of classroom climate in the learning process of a Laboratory High School in the Philippines. The result reveals that generally the respondents are satisfied with students’ services provided by the institution as manifested in their academic performance as performing are very satisfactory, thus, classroom condition has no effect on the respondents’ academic performance. More so, the -1.816 at 5% probability implies the male and female are showing the same academic performance, hence, gender differences in school achievements were not observed in this study. Further study was recommended for continues improvement of the students services provided.